Disaggregating diabetes: New subtypes, causes, and care (Medicine Anthropology Theory, 2019)
Interest in disaggregating diabetes into numerous subtypes is growing as patients and providers recognize the limitations of standard diabetes typologies. As anthropologists, we draw attention to how ‘subtyping’ may reduce stigma derived from the connection between obesity and ‘type 2 diabetes’. We highlight the complexities that drive diabetes and argue that an exclusive or dominant focus on diet and obesity obfuscates other underlying risks. Yet, we warn that subtyping may promote unnecessary pharmaceuticalization, especially for other subtypes of diabetes that may be associated with stress and inflammation. We call upon providers to continue to closely attend to patients’ lived experiences. While we recognize the shortcomings of the existing classificatory scheme, patients’ outcomes and prognoses are often more closely connected to the social and medical support they receive than to the underlying metabolic classification.